On Generalized Weakly G-Contractive Mappings in Partially Ordered G-Metric Spaces. (3rd October 2012) - Razani, A.; Parvaneh, V.
Abstract : The aim of this paper is to present some coincidence and common fixed point results for generalized weakly G -contractive mappings in the setup of partially ordered G -metric space. We also provide an example to illustrate the results presented herein. As an application of our results, periodic points of weakly G -contractive mappings are obtained.